The use of heterogeneous geospatial big data for improving decision-making - Horita, Flávio E. A.; de Albuquerque, João Porto (Anais do Concurso de Teses e Dissertações da SBC (CTD-SBC), 2018)
Emerging data sources have been increasing the amount of available and useful data, which have a potential for revolutionizing entire business processes and decisions in several scenarios, e.g., smart cities. However, at the same time that these “big data” open further opportunities, the heterogeneity of their features often hampers the integration and visualization of data. Therefore, this work presents an approach to handle heterogeneous geospatial big data for supporting a more informative decision-making. Study results advanced the state-of-the-art by understanding decision-makers' requirements and developing innovative decision support system. These indeed provided valuable contributions to practice and research.